2022
DOI: 10.1093/carcin/bgac025
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation of WTC prostate cancer tissues show signature differences compared to non-exposed cases

Abstract: There is increased incidence of prostate cancer (PC) among World Trade Center (WTC)-exposed responders and community members, with preliminary evidence suggestive of more aggressive disease. While previous research is supportive of differences in DNA methylation and gene expression as a consequence of WTC exposure, as measured in blood of healthy individuals, the epigenetics of WTC PC tissues has yet to be explored. Patients were recruited from the World Trade Center Health Program. Non-WTC PC samples were fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“… 61 It is worth noting, however, that several classes of gene pathways reported as overrepresented among WTC-exposed breast cancer cases have been consistently observed, both in our previous pilot studies of WTC exposure among cancer-free women 27 and breast cancer cases, 28 but also in an analysis of the DNA methylation profiles of WTC-exposed versus unexposed prostate cancer cases. 62 These included immune system-related gene pathways, as well as those related to cancer and cell mobility alterations. 63 Interestingly, the endocytosis pathways were consistently observed to be dysregulated among WTC-exposed individuals.…”
Section: Discussionmentioning
confidence: 99%
“… 61 It is worth noting, however, that several classes of gene pathways reported as overrepresented among WTC-exposed breast cancer cases have been consistently observed, both in our previous pilot studies of WTC exposure among cancer-free women 27 and breast cancer cases, 28 but also in an analysis of the DNA methylation profiles of WTC-exposed versus unexposed prostate cancer cases. 62 These included immune system-related gene pathways, as well as those related to cancer and cell mobility alterations. 63 Interestingly, the endocytosis pathways were consistently observed to be dysregulated among WTC-exposed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We previously described epigenetic profiles from the blood of cancer-free WTC Survivors [35] as well as Survivors with breast cancer [36] and prostate tumor tissue of Responders [37]. In each of these epigenome-wide association studies (EWAS), we found evidence of global and site-specific WTC-associated DNA methylation changes.…”
Section: Introductionmentioning
confidence: 91%
“…Pathologist review and microdissection were performed to ensure that tumor cells comprised more than 80% of formalinfixed paraffin-embedded (FFPE) tumor tissue samples. DNA was extracted, restored, and bisulfite-treated before being hybridized to the MethylationEPIC array BeadChip (Illumina Inc., San Diego, CA, USA) [37].…”
Section: Sample Collection and Processingmentioning
confidence: 99%
See 2 more Smart Citations